To simplify the square root of 60, we can start by factoring 60 into its prime factors.
-
The prime factorization of 60 is: \[ 60 = 2^2 \times 3 \times 5 \]
-
We can now express the square root: \[ \sqrt{60} = \sqrt{2^2 \times 3 \times 5} \]
-
Using the property of square roots that states \(\sqrt{a \times b} = \sqrt{a} \times \sqrt{b}\), we can separate the factors: \[ \sqrt{60} = \sqrt{2^2} \times \sqrt{3} \times \sqrt{5} \]
-
Simplifying \(\sqrt{2^2}\): \[ \sqrt{60} = 2 \times \sqrt{3} \times \sqrt{5} \]
-
Now, combining \(\sqrt{3} \times \sqrt{5}\): \[ \sqrt{60} = 2 \times \sqrt{15} \]
Thus, the simplified form of \(\sqrt{60}\) is: \[ \sqrt{60} = 2\sqrt{15} \]
This is the exact answer.